Circular RNAs and their emerging roles as diagnostic and prognostic biomarkers in ovarian cancer. (31st March 2020) - Sheng, Rong; Li, Xiaoduan; Wang, Ziliang; Wang, Xipeng
Abstract: Ovarian cancer (OC), one of the gynecologic malignancies with high invasive and metastatic potential, has a low survival rate in females. Although cytoreductive surgery combined with chemotherapy is the principal treatment for OC, the prognosis remains poor, and the recurrence rate of OC remains high. It is urgent to explore novel biomarkers for the diagnosis and prognosis of OC, as well as therapeutic targets. Circular RNAs (circRNAs) are a class of highly conserved, stable and abundant noncoding RNAs (ncRNAs). Recent studies have shown that circRNAs participate in OC progression by regulating various processes, including cell proliferation, migration, invasion and apoptosis. In addition, circRNAs are potential biomarkers for OC diagnosis and prognosis. This review provides an overview of recent findings on circRNAs in OC, including their functions and molecular mechanisms, and discusses their potential roles as diagnostic and prognostic biomarkers, as well as therapeutic targets for OC. Highlights: Classification and functions of Circular RNAs. Circular RNAs and their possible molecular mechanisms in the progression of ovarian cancer. Potential roles as diagnostic and prognostic biomarkers of circular RNAs in ovarian cancer.